Generalization of NMDA-Receptor Antagonists to the Discriminative Stimulus Effects of κ-Opioid Receptor Agonists U-50,488H, but Not TRK-820 in Rats - Tomohisa Mori; Mutsuko Nomura; Kazumi Yoshizawa; Hiroshi Nagase; Toshiko Sawaguchi; Minoru Narita; Tsutomu Suzuki (Elsevier, 2006)
Abstract.: Generalizations of NMDA-receptor antagonists to the discriminative stimulus effects of κ-opioid receptor agonists in rats were examined. Phencyclidine, MK-801, and ketamine, noncompetitive NMDA-receptor antagonists, generalized to the discriminative stimulus effects of U-50,488H, but not those of TRK-820, whereas (±)-3-(2-carbaxypiperazine-4-yl) propyl-1-phosphonic acid (CPP), a competitive NMDA-receptor antagonist, and ifenprodil, an NR1/NR2B NMDA-receptor antagonist, did not, suggesting that non-competitive NMDA-receptor antagonists possess U-50,488H-like discriminative stimulus effects in rats. Since U-50,488H and phencyclidine both induce aversive effects, our findings indicate that the cue of the discriminative stimulus effects of U-50,488H and non-competitive NMDA-receptor antagonists may be associated with their aversive effects. Keywords:: drug discrimination, κ-opioid receptor agonist, NMDA-receptor antagonist